PROSPECTS AND PROBLEMS OF IMPROVING THE LEGAL SERVICE IN THE NATIONAL GUARD OF THE REPUBLIC OF UZBEKISTAN - Colonel Abdullayev Zafarjon Nurmukhammadovich; Mamatov Shukhratjon Dilshod ugli. (Scholar Express Journals, 2022)
This article includes studying the activities of the juridical service in the system of the National Guard of the Republic of Uzbekistan and its problems, finding a scientifically based solution, as well as further suggestions to develop the sector
Keywords: Juridical sercive; jurist; juristconsult; juridical bureau